Arabic Phonetics and Phonemics Instruction in Islamic Boarding School for Children - Akla, Akla; Muyassaroh, Muyassaroh (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This study examines the learning process of Arabic phonetics and phonemics, focusing on how teachers create effective learning environments and their impact on students’ skills in an Islamic boarding school. The research used a mixed-method approach and involved young santri at Pondok Pesantren Al Imam Metro Kibang, East Lampung. Data were collected through observation, questionnaires, and tests, all validated for content. Findings reveal that students utilize strategies such as imitation, repetition with rhythmic beats, and differentiation in learning. Teachers play a crucial role by making lessons relevant, fostering commitment, and creating a cheerful, engaging classroom atmosphere. Statistical analysis confirms the significant influence of the teacher’s approach on improving students’ Arabic phonetic and phonemic abilities, with a sig value (2-tailed) of 0.000, indicating H1 acceptance. This underscores the effectiveness of teacher-guided learning in enhancing language acquisition among santri.